Your Own Personal Jesus. Expériences d’un télé-dispositif spéculatif dans Devs d’Alex Garland (2020) - Occitane Lacurie (ReS Futurae)
By studying the figures and media that inform the machine imagined by Alex Garland in DEVS, this article proposes an archaeology of this invention that lies at the crossroads of various problems of contemporary media theory and that aims to answer, in the words of speculative science fiction, the question of spatiotemporal ubiquity, inspired by a precise technological context: Californian tech.